2002
DOI: 10.1063/1.1445422
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the turbulent energy dissipation rate

Abstract: The one-dimensional surrogate for the dimensionless energy dissipation rate Cε is measured in shear flows over a range of the Taylor microscale Reynolds number Rλ, 70≲Rλ≲1217. We recommend that Cε should be defined with respect to an energy length scale derived from the turbulent energy spectrum. For Rλ≳300, a value of Cε≈0.5 appears to be a good universal approximation for flow regions free of strong mean shear. The present results for Cε support a key assumption of turbulence—the mean turbulent energy dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 11 publications
14
116
1
1
Order By: Relevance
“…Such a breakdown of classical conservation laws of the fluid equations under turbulent conditions is not unprecedented. For example, it is well-known that energy is not conserved in the limit of small viscosity for hydrodynamic turbulence, as observed both in laboratory experiments [14,15,16,17] and high-resolution numerical simulations [18,19]. A fundamental explanation for this phenomenon was proposed in 1949 by Lars Onsager [20], who showed that solutions of the ideal incompressible Euler equations do not need to conserve energy if they are sufficiently singular.…”
Section: H Alfvén (1942)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a breakdown of classical conservation laws of the fluid equations under turbulent conditions is not unprecedented. For example, it is well-known that energy is not conserved in the limit of small viscosity for hydrodynamic turbulence, as observed both in laboratory experiments [14,15,16,17] and high-resolution numerical simulations [18,19]. A fundamental explanation for this phenomenon was proposed in 1949 by Lars Onsager [20], who showed that solutions of the ideal incompressible Euler equations do not need to conserve energy if they are sufficiently singular.…”
Section: H Alfvén (1942)mentioning
confidence: 99%
“…Because of the additional normal velocity component (17), the field lines now slip through the plasma and Alfvén's "frozen-in" property is violated at length-scale ℓ.…”
Section: The Filtering Approach and Large-scale Flux Balancementioning
confidence: 99%
“…[5] and references therein) and experimental (see Refs. [6,7,8] for recent results) efforts to determine the value of C ε and its dependence on the Reynolds number. Perhaps the most convincing of these are the numerical attempts since there is no re-course to one-dimensional surrogacy as there is for experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the normalized energy dissipation rate C ε is a constant of approximately 0.5 for a wide range of Reynolds numbers, including both laboratory flows and flows in the atmosphere (Burattini et al, 2005;Pearson et al, 2002;Sreenivasan, 1998). This observation has also been called the "zeroth law of turbulence", as Kolmogorov's hypotheses assume that the mean energy dissipation rate is independent of the viscosity at high Reynolds numbers (Frisch, 1995;Pearson et al, 2004).…”
Section: Large-scale Turbulencementioning
confidence: 98%